A retrieval analysis of the Precice intramedullary limb lengthening system. Issue 7 (July 2018) - Panagiotopoulou, V. C.; Davda, K.; Hothi, H. S.; Henckel, J.; Cerquiglini, A.; Goodier, W. D.; Skinner, J.; Hart, A.; Calder, P. R.
Abstract : Objectives: The Precice nail is the latest intramedullary lengthening nail with excellent early outcomes. Implant complications have led to modification of the nail design. The aim of this study was to perform a retrieval study of Precice nails following lower-limb lengthening and to assess macroscopical and microscopical changes to the implants and evaluate differences following design modification, with the aim of identifying potential surgical, implant, and patient risk factors. Methods: A total of 15 nails were retrieved from 13 patients following lower-limb lengthening. Macroscopical and microscopical surface damage to the nails were identified. Further analysis included radiology and micro-CT prior to sectioning. The internal mechanism was then analyzed with scanning electron microscopy and energy dispersive x-ray spectroscopy to identify corrosion. Results: Seven male and three female patients underwent 12 femoral lengthenings. Three female patients underwent tibial lengthening. All patients obtained the desired length with no implant failure. Surface degradation was noted on the telescopic part of every nail design, less on the latest implants. Microscopical analysis confirmed fretting and pitting corrosion. Following sectioning, black debris was noted in all implants. The early designs were found to have fractured actuator pins and the pin and bearings showed evidence of corrosive debris. The latest designs showed evidence of biological deposits suggestive of fluid ingress within the nail but no corrosion. Conclusion: This study confirms less internal corrosion following modification, but evidence of titanium debris remains. We recommend no change to current clinical practice. However, potential reuse of the Precice nail, for secondary limb lengthening in the same patient, should be undertaken with caution. Cite this article : V. C. Panagiotopoulou, K. Davda, H. S. Hothi, J. Henckel, A. Cerquiglini, W. D. Goodier, J. Skinner, A. Hart, P. R. Calder. A retrieval analysis of the Precice intramedullary limb lengthening system. Bone Joint Res 2018;7:476–484. DOI: 10.1302/2046-3758.77.BJR-2017-0359.R1.